Implementasi Kompetensi Manajerial Kepala Sekolah dalam Menyusun Perencanaan Strategik Pendidikan - Suharyanto H. Soro; Yoyon Pujo Utomo; Rica Agus Budiyanto; Chici Riska Kusuma Dewi (LP. Ma'arif Janggan Magetan, 2024)
The managerial competence of school principals plays an important role in improving the quality of school administration services in the digital era. This is one of the keys to creating information technology (IT)-based school administration services. In other words, utilizing technology is mandatory in order to create a more efficient, transparent and integrated system. This research aims to exploit the managerial competence of school principals as leaders in educational units in preparing information technology-based educational strategic planning and implementing it in the school administration process. Researchers use a case study approach. This approach is one of the qualitative research paradigms. Data collection methods use observation, interviews and documentation methods. The research results show that (1) the managerial competence of school principals is an inseparable part of administrative governance which is supported by information technology so that schools can improve the quality of their education; (2) The existence of information technology-based school administration management has a positive impact on effective and transparent school management; (3) The school principal as a policy and decision maker in the management of school administration feels light and trusted because the results are based on data or based on information technology implemented in his school.